Pengembangan UMKM Produk Alen-Alen Bu Wati Melalui Pemanfaatan Platform Instagram - Irdlin Hanifah; Putri Kharisma Ayuningtiyas; Ines Kiki Faradila Hardika Dini; Lailatul Fadilah; Bintis Tianatud Diniati (Jurnal Ekonomi dan Bisnis Digital, 2024)
This This study examines Alen-Alen Bu Wati's efforts to develop micro, small and medium enterprises (MSMEs) by using the Instagram platform as a digital marketing tool. The use of social media such as Instagram in the modern era allows MSMEs to increase the visibility of their products, reach more customers, and build stronger relationships with existing customers. Using qualitative data collection methods, this research investigates business owners directly and analyzes sales data before and after using Instagram as a promotional tool. The aim of this process is to radiate how effective digital marketing strategies are to overcome conventional marketing problems and increase product competitiveness in the wider market. Research shows that the use of Instagram significantly increases sales of Bu Wati's alen-alen and increases product market share, attracting customers at local and international levels. To attract audience attention, an approach of engaging visual content and consistent interaction with customers has proven successful. This study found that Instagram can be an important marketing tool for the sustainability of MSMEs in the digital era, especially in terms of increasing market access and increasing business profits.